Parental investment without kin recognition: Simple conditional rules for parent-offspring behavior - Aktipis, C. Athena (2010)
Species differ widely with regard to parental investment strategies and mechanisms underlying those strategies. The passing of benefits to likely offspring can be instantiated with a number of different computational and behavioral systems. We report results from an agent-based model in which offspring maintain proximity with parents and parents transmit benefits to offspring without the capacity of either parent or offspring to ‘recognize’ one another. Instead, parents follow a simple rule to emit benefits after reproducing and offspring follow a simple rule of moving in the direction of positive benefit gradients. This model differs from previous models of spatial kin-based altruism in that individuals are modeled as having different behavioral rules at different life stages and benefits are transmitted unidirectionally from parents to offspring. High rates of correctly directed parental investment occur when mobility and sociality are low and parental investment occurs over a short period of time. We suggest that strategies based on recognition and bonding/attachment might serve to increase rates of correctly directed parental investment under parameters that are shown here to otherwise lead to high rates of misdirected and wasted parental investment.